Investigating the influence of lean six sigma practices on quality performance in medical device manufacturing industry / Sim Choon Ling...[et al.] - Sim, Choone Ling; Jusoh, Muhammad Shahar; Akmar Ishak, Noormaizatul (Universiti Teknologi MARA, Kedah, 2019)
With the growing pressure to gain optimum level of quality and speed, Lean and Six Sigma practices have been acknowledgedas viable alternatives for process improvement. Separately, both methodologies were unable to drive process improvement to its full potential thus recent years have witnessed greater tendency for Lean and Six Sigma practices to be implemented in an integrated way. This paper attempted to highlight the key strengths, weaknesses and criticisms of Lean and Six Sigma practices as a separate methodology as well as an overview on how the two methodologies complement each other into a more robust and comprehensive approach. Furthermore, although there is a growing body of anecdotal evidence in supporting the positive linkage of Lean Six Sigma (LSS) practices in enhancing quality performance nevertheless the abundance of non-empirical evidence on whether the integration of Lean and Six Sigma practices is tied to superior performance improvement than either on a standalone basis has triggered the needs to further verifying this issue. The objective of this paper is to define and develop an agenda for future research to investigate the impact of LSS practices on quality performance in medical device manufacturing (MDM) industry.